The Herpetofauna of the Caribbean Islands San Andres and Providencia - Tamsitt, J. R. (1963)
The herpetofauna of the Caribbean Islands of San Andrés and Providencia consists of one frog, two turtles, eíght lizards and three snakes. According to areas of most probable origín, three species are derivable from Jamaica and the southern Lesser Antilles, two from Darién or the mainland of South America, and nine from Central America. The herpetofauna clearly shows mainland rather than West Indian affinities, and introductions by human agency since the arrivaL of the first settlers in 1629 have been important.